The Effect of Perceived Security, Perceived Ease of Use, and Perceived Usefulness on Interest in Using Linkaja E-Wallet in Mataram City - Ardila, Dinda Dwi; Athar, Handry Sudiartha (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to determine the influence of Perceived Security, Perceived Ease of Use, and Perceived Usefulness on the Interest in Using LinkAja E-wallet in Mataram City. The sample in this study amounted to 112 respondents taken using probability sampling with purposive sampling technique. Data collection used a questionnaire with a Likert scale of 1-5. The analytical tool used is multiple linear regression analysis using SPSS Software Version 27 Classical assumption testing, partial testing (t-test), simultaneous testing (f-test) and coefficient of determination (R2). The results of this study indicate that the variable Perceived Security (X1) has a negative and significant effect on Interest in Using (Y). Meanwhile, the variables Perceived Ease of Use (X2) and Perceived Usefulness (X3) have a positive and significant effect on Interest in Using (Y).